Antibody repertoire profiling with mimotope arrays - Shina Pashova; Christoph Schneider; Stephan von Gunten; Anastas Pashov (Taylor & Francis Group, 2017)
Large-scale profiling and monitoring of antibody repertoires is possible through next generation sequencing (NGS), phage display libraries and microarrays. These methods can be combined in a pipeline, which ultimately maps the antibody reactivities onto defined arrays of structures - peptides or carbohydrates. The arrays can help analyze the individual specificities or can be used as complex patterns. In any case, the targets recognized should formally be considered mimotopes unless they are proven to be epitopes driving the antibody synthesis. Here, the advantages and disadvantages of the major profiling techniques as well as their current and future application in disease prediction and vaccination are discussed.